The Role of Management Information Systems and Digital Asset Management in Enhancing the Effectiveness of Regional Asset Control: Evidence from the Government of West Sulawesi Province, Indonesia - Andi Muhammad Angkasa; Hari Yeni; Sri Darmawansyah; Rahmiati (PT. LITERASI SAINS NUSANTARA, 2026)
Digital transformation has become a strategic priority for improving governance and accountability in public sector organizations. In regional governments, the implementation of Management Information Systems (MIS) and Digital Asset Management (DAM) is expected to strengthen the effectiveness of regional asset control by improving information quality, administrative efficiency, and organizational transparency. However, empirical evidence regarding the combined influence of these digital capabilities on regional asset governance remains limited, particularly within Indonesian provincial governments. This study therefore investigates the effects of Management Information Systems and Digital Asset Management on the effectiveness of regional asset control in the Government of West Sulawesi Province. A quantitative research design was employed using a cross-sectional survey of 108 employees directly involved in regional asset management, including asset administrators, information system operators, and asset administration officials. Data were collected through structured questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics. The findings reveal that both Management Information Systems and Digital Asset Management have positive and statistically significant effects on the effectiveness of regional asset control. Management Information Systems improve administrative efficiency, information quality, and decision-making capability, while Digital Asset Management enhances real-time monitoring, information integration, asset security, and reporting efficiency. Furthermore, the two variables jointly explain 59.2% of the variation in regional asset control effectiveness, highlighting the strategic importance of digital transformation in strengthening public asset governance. This study contributes to the literature by extending the application of the Resource-Based View and the Information Systems Success Model to regional government asset management. Practically, the findings provide evidence that integrated digital information systems and digital asset management practices can improve transparency, accountability, and operational efficiency, thereby supporting the implementation of good governance within regional governments.